Reflections on Portraiture: Unifying the Face and Pluralizing Personality - van Alphen, Ernst (Artium Quaestiones, 2024)
Two assumptions play an important role in the study of portraiture 1) Studies of the portrait are usually based on the idea that the face that is shown in the portrait is also a portrait in its own right, namely, a portrait of the soul of the portrayed person. 2) The main function of portraiture is to portray or even capture the unique, personal identity of a person; that identity is an essential and stable entity. In this paper, both assumptions will be challenged. As a result, portrait and face should not be conflated and arguments on the face have a quite different status than those on portraits. Concerning the second assumption, surrealist portraits and contemporary portraiture suggest the opposite of an essential personality that does not change over time: when portraits are remade after some time, different personalities present themselves. This does not mean that a unique personality or identity does not exist per se, but that portraiture cannot be used to make this claim.